2015
DOI: 10.17957/ijab/15.0001
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Nickel-Induced Stress in Mungbean through Application of Gibberellic Acid

Abstract: ). Two sets of Ni contamination levels were maintained, one set was kept without application of GA 3 while in second set 10 -4 M GA 3 was applied as foliar spray at 15, 30 and 45 days after germination. Significant reduction in all growth and yield attributes of mungbean was recorded in Ni contaminated pots. However, application of GA 3 enhanced the length, fresh and dry weight of shoots and roots as well as grain yield of mungbean in Ni contamination. Moreover, Ni concentration was increased in roots and shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The result showing the significant difference in the plant height agrees with the study of Ali et al. [ 17 ], where the application of GA 3 enhanced Mung bean plant growth under Ni stress. Studies on the effect of HMs on plants have shown that HMs are detrimental at levels higher than a certain threshold [ 18 ].…”
Section: Resultssupporting
confidence: 91%
“…The result showing the significant difference in the plant height agrees with the study of Ali et al. [ 17 ], where the application of GA 3 enhanced Mung bean plant growth under Ni stress. Studies on the effect of HMs on plants have shown that HMs are detrimental at levels higher than a certain threshold [ 18 ].…”
Section: Resultssupporting
confidence: 91%
“…This reaction was rather unusual, since GA3 was reported to be involved in alteration of the membrane permeability and regulation of membrane transport processes, leading to a decrease in metal uptake (Rubio et al 1994 ; Moya et al 1995 ). This reduction of Ni accumulation in GA3-treated plants was observed in Ni-hyperaccumulating species of Alyssum and Noccaea (Cabello-Conejo et al 2014 ) or non-accumulating specimens of Vigna radiata (Ali et al 2015 ).…”
Section: Discussionmentioning
confidence: 75%
“…Kumchai et al (2013) studied the role of proline to partially prevail over molybdenum induced stress in cabbage seedling. Plant hormone Gibberellic acid has the potential to alleviate Ni induced stress; it has been proven by the Ali et al (2015) in mungbeen plant. They further propounded that the application of gibberellic acid on mungbeen improved plant growth and yield.…”
Section: Ameliorating Mechanism Of Benificial Heavy Metal Toxicitymentioning
confidence: 99%